Transparent Thiol‐ene/Acrylate‐Based MicroECoG Devices Used for Concurrent Recording of Fluorescent Calcium Signals and Electrophysiology in Awake Animals. Issue 25 (2nd August 2022) - Szabó, Ágnes; Madarász, Miklós; Lantos, Zsófia; Zátonyi, Anita; Danda, Vindhya; Spurgin, Lisa; Manz, Connie; Rózsa, Balázs; Fekete, Zoltán
Abstract: Shape memory polymers (SMPs) are suitable substrate materials for soft neural interfaces due to their tunable elastic characteristics. The stability and biocompatibility of intracortical SMP probes are demonstrated. In this work, a SMP‐based cortical implant capable of recording high‐density micro‐electrocorticography is utilized in a multimodal neuroimaging scheme. The transparent nature of thiol‐ene/acrylate substrate is exploited, and the feasibility of measuring intracranial electroencephalogram and fluorescent GCaMP6 signals with two‐photon imaging through the device is presented in mice. The potential influence of the optical properties of the microdevice is investigated using fluorescent microbeads, hippocampal brain slices, and awake animals. It is found that neurites and cell soma can be efficiently detected with sufficient resolution to follow changes in the calcium signal. These chronically implanted devices do not suppress the quality of optical signals exceeding 22 weeks after implantation. These results indicate that thiol‐ene/acrylate ECoG is an appropriate tool to combine electrophysiology with two‐photon imaging while leveraging the inherent tissue‐friendly properties of SMPs. Abstract : Soft, transparent thiol‐ene/acrylate‐based neural microimplant is utilized to concurrently record cortical electrophysiology and optical signals with two‐photon calcium imaging. Ca signals of individual neurons can be recorded for at least 22 weeks in awake animals at high spatial resolution. Integrated gold and iridium‐oxide electrodes provide stable signal‐to‐noise ratio during the long‐term in vivo experiment.